A Critique of the Effectiveness of Cyber Laws in Addressing Cyber Harrassment - Mariam Mirembe (Uganda Christian University, 2025)
Cyber harassment is the use of a computer for making any requests, suggestions or proposals which is obscene, lewd, lascivious or indecent, threatening to inflict injury or physical harm to the person or property of any person. Cyber harassment is a growing evil that has been taking place since the invention of computer chat rooms to the creation of Facebook, twitter, tiktok, among others. With the presence of these various communication forums and the ability of users to remain anonymous, cyber harassment has become a daily crime, causing its victims to suffer from depression, self-denial, isolation and sometimes suicidal thoughts. This research basically looks at the effectiveness of cyber laws such as the Computer Misuse Act Cap 96, Access to Information Act Cap 95, and Data Protection and Privacy Act Cap 97, in curbing cyber harassment. The research shall be table-based (qualitative), specifically based on the available literature on the research topic as well as the required statutes, and it shall focus on the general population as the victim to cyber harassment. This research is expected to amplify the voice in the fight against cyber harassment as well as provide new measures to help curb the evil.